The Estimation of Losses of the Russian Economy from Population Migration to Developed Countries in 2000-2017 - Maslennikov, Vladimir V.; Linnikov, Aleksandr S.; Maslennikov, Oleg V. (Journal of Reviews on Global Economics, 2018)
The problem of emigration of Russian citizens to other countries remained quite acute during 2000-2017. This poses a threat to national security, as there are many economically active young people with a high level of education among the emigrants. Therefore, it is required a comprehensive study of these processes and the creation of conditions for the preservation of human capital in Russia. The authors developed a methodology for assessing the losses of the Russian economy in value terms as a result of emigration of citizens abroad. It is based on the determination of the 'cost' of human life and the individualization of this indicator in accordance with the level of economic development of the host country and with the subjective factors of the emigrant, as well as in specifying the number of citizens who left the Russian Federation in accordance with the official data of foreign migration services. As a result of the calculations, it was determined that the losses of the Russian economy from this phenomenon for the period 2000-2017 amounted to more than 545.85 billion USD. Such a situation is unacceptable in the conditions of the country's unfolding competition with other states for the positions of leaders in the new industrial revolution. It is necessary to carry out systematic work to reduce the scale of outgoing flows of international labour migration from Russia.